Childhood maltreatment and intimate partner violence victimization: A meta-analysis. (February 2019) - Li, Sen; Zhao, Fengqing; Yu, Guoliang
Abstract: Background: Intimate partner violence (IPV) victimization is a serious public health problem in the world. It is imperative to examine risk factors for IPV victimization. Objective: This meta-analysis aimed to explore the relationship between childhood maltreatment (CM) and IPV victimization and investigate the moderating effects of gender and marital status. Participants and Setting: Examination of the literature produced a sample of 56 effect sizes ( N = 23, 127) for review. Methods: PsycINFO, PsycArticles, EBSCO-ERIC, Medline, Google Scholar, and ProQuest Dissertations & Theses databases were systematically searched until March 31, 2018. Forty-six eligible studies were included in the meta-analysis. Random effects model was used for meta-analysis of the studies. Results: Results indicated a significant association between total CM and IPV victimization ( r = .18, p < .001). Further subgroup analyses revealed that all four types of CM (childhood physical abuse, psychological abuse, sexual abuse, and neglect) were positively related to IPV victimization ( r = .19, .18, .17, and .12, respectively). Moreover, the moderation analyses revealed that the association between CM and IPV victimization was stronger for dating couples than for married ones. However, this relation did not show significant difference between males and females. Conclusions: There is an association between CM and IPV victimization, and it is moderated by marital status.